2011
DOI: 10.1007/s12564-011-9149-x
|View full text |Cite
|
Sign up to set email alerts
|

Social involvement and development as a response to the campus student culture

Abstract: Given the widely accepted notion of whole person education in Confucian societies such as Hong Kong, Mainland China and Singapore, it is surprising that research literature originated in these societies pays little attention to how students learn and develop through out-ofclass experiences at university. There is little research evidence on how the prevailing culture among student social communities (residential halls and student societies/ clubs) influences students' social involvement and development. This p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…Mos versities utilise nearby public spaces for social activity and formal and info Hecke et al [13] and Mertens et al [14] highlighted the role of space design factors and parameters in users' experience of these spaces. According to Salih et al [6] and Yang and Chau [37], informal learning spaces and their design tools in natural environments offer opportunities to enhance personal, social, and academic growth. Salih et al [6] confirmed that appropriate characteristics of these spaces contributed to the development of awareness, social improvement, and environmental benefits.…”
Section: Research Gap and Justification Of This Studymentioning
confidence: 99%
“…Mos versities utilise nearby public spaces for social activity and formal and info Hecke et al [13] and Mertens et al [14] highlighted the role of space design factors and parameters in users' experience of these spaces. According to Salih et al [6] and Yang and Chau [37], informal learning spaces and their design tools in natural environments offer opportunities to enhance personal, social, and academic growth. Salih et al [6] confirmed that appropriate characteristics of these spaces contributed to the development of awareness, social improvement, and environmental benefits.…”
Section: Research Gap and Justification Of This Studymentioning
confidence: 99%
“…Everyday learning activities typically take place in informal learning settings, also provide an emerging learning mode and contribute to the social learning experience (Rea, 2009). Yang and Chau (2011) argued that social learning settings outside of classrooms, such as student socialisation places and oncampus pocket spaces, can enhance the learning experience by offering social learning activities. Learning occurs when students interact with one another in a social context on campus (Rea, 2009;Yang and Chau, 2011); depending on the place attributes (Perkins and Will, 2014), some non-classroom contexts can provide social learning settings that promote formal and informal learning.…”
Section: Pocket Settings and Their Design Attributesmentioning
confidence: 99%
“…Yang and Chau (2011) argued that social learning settings outside of classrooms, such as student socialisation places and oncampus pocket spaces, can enhance the learning experience by offering social learning activities. Learning occurs when students interact with one another in a social context on campus (Rea, 2009;Yang and Chau, 2011); depending on the place attributes (Perkins and Will, 2014), some non-classroom contexts can provide social learning settings that promote formal and informal learning. Social learning activities could enhance students' academic skills by giving flexible spaces for learning (Yang and Chau, 2011).…”
Section: Pocket Settings and Their Design Attributesmentioning
confidence: 99%
See 2 more Smart Citations